Antioxidant activity and color of beef jerky with kluwek - A. R. Febriana; H. Hajrawati; W. Hatta (Теория и практика переработки мяса, 2025)
Spoilage that often occurs in jerky is generally caused by the fat oxidation process, either during the manufacturing process, heating, or storage, and can lead to health hazards. This study was conducted to examine the potential of kluwak as a natural antioxidant that can reduce the oxidation process, by exploring its effects on antioxidant activity and physical properties, namely L*a*b* color values and cooking loss of jerky with the addition of kluwak. Kluwak, originating from community gardens in Soppeng Regency, Makassar, Indonesia, was used as an additional ingredient in making ground beef jerky. The part of meat used was the thigh, obtained from a slaughterhouse, and different levels of kluwak — namely 0 %, 2 %, 4 %, and 6 %—were added. The research results show that the addition of kluwak to jerky increases antioxidant activity, as indicated by higher values in the antioxidant activity test using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method, which signifies increased antioxidant capacity. In addition, the use of kluwak also showed a significant effect on the color parameters a* and b*, indicating positive changes in the visual appearance of the product. However, no significant effect was found for the L* color parameter, which measures brightness, and no difference was observed in the cooking loss of the jerky. In conclusion, kluwak can function as an effective natural antioxidant in reducing fat oxidation in jerky, while providing positive changes in product color without affecting brightness or cooking loss.